Labial myiasis: clinical case report (Research, Society and Development, 2021)
Myiasis is a disease defined as an invasion of living or dead tissues of a human or vertebrate animal host by the eggs or larvae of flies of the order Diptera, which can be classified based on the area of ​​the body affected, one of which is oral myiasis, a condition which can be manifested in several locations within the oral cavity. the dental surgeon needs to be aware of cases of myiasis in the oral cavity involving adults and children, making an early diagnosis and immediate care. The objective was to describe the clinic of a rare case of labial myiasis in a victim of aggression and imprisonment, from its diagnosis, emergency treatment and resolution of the case. The involvement of myiasis in the oral and maxillofacial region is a rare occurrence, which can cause extensive sequelae for the individual and its prognosis is directly related to the time, place of occurrence and the patient's systemic conditions. The dental surgeon needs to be aware to intervene quickly and accurately, thus reducing injuries and resulting damage as well as a quick and better recovery of the patient.